2003
DOI: 10.1080/13550280390173427
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1-Induced Encephalitis has an Apoptotic Component Associated with Activation of c-Jun N-Terminal Kinase

Abstract: Herpes simplex virus type 1 (HSV-1) triggered apoptosis in hippocampal cultures, as determined by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) and immunohistochemistry with antibody specific for the large fragment of activated caspase 3. The levels of phosphorylated (activated) c-Jun N-terminal kinase (JNK) were also increased in HSV-1-infected hippocampal cultures as were the levels of activated c-Jun, its target. JNK activation was involved in HSV-1-induced apoptosis as evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…Apoptosis was determined by TUNEL, morphological alterations, caspase activation, and poly(ADP-ribose) polymerase cleavage, a crucial factor in the cell's commitment to undergo apoptosis (48), with a good degree of correlation between the various assays. The specificity of the antibodies used in these studies was previously confirmed in our and other laboratories (3,16,55,63,(66)(67)(68)(73)(74)(75)(76). Normal rabbit serum was negative in all assays.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Apoptosis was determined by TUNEL, morphological alterations, caspase activation, and poly(ADP-ribose) polymerase cleavage, a crucial factor in the cell's commitment to undergo apoptosis (48), with a good degree of correlation between the various assays. The specificity of the antibodies used in these studies was previously confirmed in our and other laboratories (3,16,55,63,(66)(67)(68)(73)(74)(75)(76). Normal rabbit serum was negative in all assays.…”
Section: Discussionsupporting
confidence: 50%
“…These included HSV-2 mutants deleted in the PK (ICP10⌬PK) or RR (ICP10⌬RR) domains of ICP10, transfection with expression vectors for ICP10 (pJW17) or its PK-negative mutant p139 (pJHL15) (3,55,(66)(67)(68)(73)(74)(75)(76), and primary hippocampal cultures that contained Ͼ88% postmitotic neurons, which have definite exons and dendrites, form synapses, are electrically active, and closely resemble neurons in vivo (5). Apoptosis was determined by TUNEL, morphological alterations, caspase activation, and poly(ADP-ribose) polymerase cleavage, a crucial factor in the cell's commitment to undergo apoptosis (48), with a good degree of correlation between the various assays.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had shown that ICP10PK inhibits caspase-dependent apoptosis triggered by various neurotoxic stimuli, [11][12][13][14][15][16][17]27 but this is the first report that it also inhibits calpaindependent PCD, underscoring its ability to override multiple death programs. The following comments seem pertinent with respect to these findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it may be significant to point out that the physiopathology of PD was also associated with death programs that were not studied in the present series of experiments, including growth factor depletion (viz nerve growth factor, NGF), 46 activation of the JNK pathway, 35 and glial cell activation and production of proinflammatory cytokines (viz tumor-necrosis factor-a, and interleukin-1b), 46 all of which are also inhibited by ICP10PK. 11,12,14,27 ICP10PK also upregulates XIAP, 12 which was also implicated in PD therapy. 35,47 We conclude that ICP10PK has a broad-spectrum neuroprotective activity, which is characterized by remarkable functional redundancy associated with the activation of survival pathways that can inhibit multiple death programs and modulate neuron-glial cell cross talk.…”
Section: Discussionmentioning
confidence: 99%
“…31 Caspase-dependent apoptosis is involved in HSV-associated injury, 32 in adrenal cells, neuronal cells, corneal cells, hepatic cells, and dendritic cells as well. [33][34][35][36][37] Recently, the association between cardiac myxoma and HSV-1 has been determined. 7 Thus, we assume that HSV-1 might induce apoptosis in myxoma.…”
Section: Discussionmentioning
confidence: 99%